Population and economic growth in developed countries. Issue 4 (4th July 2022) - Lianos, Theodore P.; Tsounis, Nicholas; Pseiridis, Anastasia
ABSTRACT: The relationship between population growth and economic growth is examined. Evidence is provided on the direction of causality between population and GDP in five industrialized countries (US, UK, Germany, France, and Italy) for the periods 1820–1938 and 1950–2016. Using Toda-Yamamoto Granger causality tests and Sims causality test it was found that the direction of causality during the former period was from Population to GDP or bidirectional while for the latter period, it was from GDP to population. It is also shown that during the second period per capita GDP was almost double relative to the first period. We argue that the difference may be partly explained by the direction of causality between the two variables. In the 1820–1938 period, the direction of causality is probably due to the large family model that prevailed in that period that led to rapid population growth. For the 1950–2016 period it is probably the rapid economic growth that followed the Second World War and motivated large migration flows to the developed countries we examined.